2014
DOI: 10.1007/s12262-014-1122-6
|View full text |Cite
|
Sign up to set email alerts
|

Foregut Duplication Cyst Associated with Esophageal Atresia—One-Stage Neonatal Surgical Repair

Abstract: Foregut duplication cysts can occur anywhere along the foregut-derived structures. Its association with esophageal atresia (EA) and tracheoesophageal fistula (TEF) is exceptionally rare, the majority of cases being diagnosed at an older age due to symptoms or complications. We present the third reported case in the literature, when diagnosis and treatment were done at the time of repair for EA-TEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…The second milestone of H-TOF surgery is its intraoperative identification. In extremely rare cases, but possible as previously reported, the fistula may be associated with a duplication cyst which may enable difficulty in its identification and dissection (26). We discussed this above along with the advantages of tracheobronchoscopy.…”
Section: Discussionmentioning
confidence: 82%
“…The second milestone of H-TOF surgery is its intraoperative identification. In extremely rare cases, but possible as previously reported, the fistula may be associated with a duplication cyst which may enable difficulty in its identification and dissection (26). We discussed this above along with the advantages of tracheobronchoscopy.…”
Section: Discussionmentioning
confidence: 82%
“…The results of the current research uncovered that there were noticeably more cases of postoperative vascular embolism and anaemia in the control group than those in other experimental groups, which indicated that TXA was safe and feasible for surgical application, and also did not increase the risk of concurrent vascular embolism events [25]. However, the number of patients in the S4 group with complicated vascular embolism was markedly higher than that in the S1, S2 and S3 groups, which reflected that the high dose of TXA administered at 60 mg/kg bw may lead to the risk of postoperative complicated vascular embolism [25][26][27][28]. Also, plasma levels of TNF-α, IL-1, IL-6 and IL-8 were compared before and after the operation in the S2 group and the control group, and it was disclosed that the levels of TNF-a, IL-1, IL-6 and IL-8 in the S2 group were significantly decreased compared with those in the control group (p < 0.05), which indicated that TXA had an antiinflammatory effect on different stages of the systemic inflammatory response induced by surgery, possibly because TXA can indirectly play an anti-inflammatory role by protecting inflammation-related PTs [27].…”
Section: Peripheral Blood Mononuclear Cells (Pbmcs) Expression In the S2 Group And D0 Groupmentioning
confidence: 89%
“…If the cyst content is only evacuated, the left mucosa may lead to hemorrhage and anemia, recurrent pancreatitis, rupture, or malignant degeneration. Enucleation of the duplication of the cyst allows preservation of the esophageal wall length, which is essential in primary esophageal anastomosis [ 14 ]. Gastric duplications are misdiagnosed as cystic tumors of the pancreas [ 15 ] or adrenal gland but with normal tumor markers or in rare cases the ectopic tissue can be a cause of gastrointestinal bleeding.…”
Section: ⧉ Discussionmentioning
confidence: 99%